2003
DOI: 10.1248/bpb.26.210
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Predict the Ductus-Arteriosus Dilating Effect Induced by Lipo-Prostaglandin E1 in Newborn Rats Lacking Plasma Concentration-Time Data by the Pharmacological Response Kinetic Model.

Abstract: selectively dilate ductus arteriosus in many mammal neonates.1) A cyclodextrin preparation of PGE 1 (PGE 1 -CD)2) and a lipid microsphere preparation of PGE 1 (lipo-PGE 1 ) 3,4) have both been widely used in emergency treatment in neonatal patients with ductus dependent congenital heart diseases (D-CHDs). However, a fatal adverse drug reaction, apnea, may occur when PGE 1 is overdosed.5) Lipo-PGE 1 is a passive targeting-type drug delivery system (DDS) of PGE 1 , in which PGE 1 is dissolved in the lipid emulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…When superabundant hydrosoluble solvents are added, demulsification is easy to be caused, which would decrease the targeting effect of the preparation and reduce the therapeutic efficacy. Moreover, demulsification may cause the leakage of prostaglandin E 1 , which is an inflammatory factor and heat source, and then cause adverse reactions such as phlebitis [24]. We found that before intervention Lipo-PGE 1 was always diluted by inappropriate menstruum such as invert sugar injection, multiple electrolytes and invert sugar injection, which are expensive and include fructose.…”
Section: Discussionmentioning
confidence: 91%
“…When superabundant hydrosoluble solvents are added, demulsification is easy to be caused, which would decrease the targeting effect of the preparation and reduce the therapeutic efficacy. Moreover, demulsification may cause the leakage of prostaglandin E 1 , which is an inflammatory factor and heat source, and then cause adverse reactions such as phlebitis [24]. We found that before intervention Lipo-PGE 1 was always diluted by inappropriate menstruum such as invert sugar injection, multiple electrolytes and invert sugar injection, which are expensive and include fructose.…”
Section: Discussionmentioning
confidence: 91%
“…When superabundant hydrosoluble solvents are added to this formulation, the demulsi cation is easy to be caused, which would decrease its targeting effect and therapeutic e cacy. Moreover, demulsi cation may lead to the leakage of prostaglandin E1, an in ammatory factor and heat source, which stimulates blood vessels to produce serotonin and bradykinin, thus increasing capillary permeability and causing adverse reactions, such as phlebitis 29,30 . In our study, we found that Lipo-PGE 1 was always diluted by large amount of inappropriately solvents (0.02 or 0.04 or 0.1 µg/mL), such as invert sugar injection, multiple electrolytes and invert sugar injection, which include fructose, un-suitable for patients with hyperuricemia and gout, and were expensive.…”
Section: Discussionmentioning
confidence: 99%
“…When superabundant hydrosoluble solvents are added to this formulation, the demulsification is easy to be caused, which would decrease its targeting effect and therapeutic efficacy. Moreover, demulsification may lead to the leakage of prostaglandin E1, an inflammatory factor and heat source, which stimulates blood vessels to produce serotonin and bradykinin, thus increasing capillary permeability and causing adverse reactions, such as phlebitis 31 , 32 . In our study, we found that Lipo-PGE 1 was always diluted by large amounts of inappropriate solvents (0.02 or 0.04 or 0.1 μg/mL), such as invert sugar injection, multiple electrolytes, and invert sugar injection, which include fructose, unsuitable for patients with hyperuricemia and gout, and were expensive.…”
Section: Discussionmentioning
confidence: 99%